Strengthening Safeguards in Bank Resolution Frameworks in Emerging and Developing Countries - Jansen, Barend; Rawlins, Marlon Rolston; Zanforlin, Luisa (World Bank, Washington, DC, 2020)
This paper takes a closer look at why safeguards are needed in bank resolution frameworks and how the principles included in a subset of the key attributes are expected to protect third party rights. Through a review of a set of issues encountered across a sample of 12 emerging and developing countries from 6 regions, the authors seek to highlight areas where safeguards may not easily be implemented, highlighting the potential need for legislative amendments, or a thorough review of administrative procedures, and or significant capacity development of the judicial profession.